Housing and Permanent Income: Tests Based on a Three-Year Reinterview Survey - Lee, Tong Hun (The Review of Economics and Statistics, 1968)
U NTIL the mid-1950's, the traditional view on the consumption of housing had been that the elasticity of housing consumption with respect to current income was less than unity.' However, recent literature on the theory of consumption function [15] [4] has pointed out that, in relating income to consumption, the concept of income should be that of permanent income rather than current or measured income, and that the use of measured income imparts a downward bias in estimating the effect of permanent income on consumption. Since housing consumption in particular may also be affected by the long-run prospect of income rather than by a single-year measured income, the permanent income elasticity may be higher than the previous estimates of the measured income elasticity of housing. The change in the concept of income encouraged a number of economists to test the effect of permanent income on housing consumption. Maisel and Winnick [14] tested the permanent income hypothesis of housing consumption by utilizing the I950 Survey of Consumer Expenditures. Contrary to the permanent income hypothesis, however, they reported that housing consumption was no more responsive to changes in permanent income than to changes in measured current income. Subsequently Margaret Reid [19] conducted an extensive cross-sectional study by using housing and income data obtained primarily from the 1950 Housing Census. Differing from Maisel and Winnick, Reid found that the demand for housing was indeed more responsive to changes in permanent income. Moreover, Reid's estimates of the permanent income elasticity of housing were substantially greater than one, and in fact ranged from 1.5 to 2. On the other hand, the author's recent time-series analyses [10] [11] indicated that while housing demand was more responsive to changes in permanent income, the permanent income elasticity of housing was still less than unity. The purpose of this paper is to obtain the cross-sectional estimates of permanent income elasticity on the basis of the 1960-1961-1962 reinterview Surveys of Consumer Finances. This study has three distinct features. First, this study differs from other housing studies in that it uses the instrumental variable method along the lines suggested by Livitan [12]. Livitan has recently shown that, for any year of analysis, the use of a lagged or future measured income as an instrumental variable yields a powerful test of the permanent income hypothesis. Second, since this study utilizes threeyear reinterview data, as a result both one-year and two-year lagged or future incomes can be used as instrumental variables. Due to the lack of data, Livitan [12] could not experiment with a two-year lagged or future income as an instrumental variable in his analysis of total consumption. Both Livitan [13] and Friedman [5], however, agreed that it is highly desirable to use a two-year lagged or future income as an instrumental variable. Finally, this paper develops and uses an extended version of Livitan's instrumental variable method in order to take account of the case in which a lagged or future income may not be a perfect instrumental variable for permanent income. The cross-sectional estimates of permanent income elasticity so estimated are substantially * The author is Professor of Economics at the University of Wisconsin-Milwaukee and a member of the Social Systems Research Institute at the University of Wisconsin, Madison. He is grateful to Melvin Lurie and Keith Phillips for their helpful comments on the initial draft of this paper. The author, however, remains responsible for the views expressed in this paper. This study was originally supported by the National Science Foundation under grant GS-631 and later by the Graduate School of the University of Wisconsin-Milwaukee. The data used in the study originally came from the Surveys of Consumer Finances conducted by the Survey Research Center, University of Michigan, in cooperation with the Board of the Governors of the Federal Reserve System. The author is indebted to the Social Systems Research Institute for making available the data coded on magnetic tapes. 1 For a brief account of the early history of housing studies, see the author's paper [10, pp. 82-83].